Relevance of the Fatwa of the Indonesian Ulema Council to the Renewal of Islamic Family Law in Indonesia (Study of MUI Fatwa Number: 4/Munas VII/MUI/8/2005 on Marriage of Different Religions) - Puad Muzakkar Siregar (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2021)
Fatwa is a practical law similar to fiqh (al-ahkâm al-’amaliyah). Therefore, the fatwa must be context-bound; context of time (tempus), place (locus), context of natural conditions, social context, demographic context, and other contexts. In the Indonesian context, the Indonesian Ulema Council (MUI) is the official state-recognized institution to issue fatwas as guidelines for Indonesian Muslims. This paper answers two questions: how is the MUI fatwa related to the legal status of interfaith marriages? Furthermore, is the MUI fatwa on interfaith marriage relevant to the reform of Islamic family law in Indonesia? As a result, although many scholars allow interfaith marriages because Muslim men and women are experts of the book, the MUI fatwa forbids interfaith marriages based on sadd al-dzari’ah to prevent negative impacts. This is a family law product with a renewal side, because it is responsive to social dynamics and changing times, by prioritizing the benefit based on maqasid shari’ah